The Art of War - Tzu, Sun; Wilson, Andrew, Dr. (London : FLAME TREE PUBLISHING, 2020)
Focusing on military strategy, psychology and tactics, The Art of War has been a source of great strategic inspiration throughout the ages and its enduring wisdom has had a far-reaching impact beyond its Ancient Chinese origins. This new edition offers a comprehensive new introduction, with commentary and notes on the core text.
Keywords: War -- Early works to 1800; Military art and science -- Early works to 1800.; Military art and science